The facilitator's guide to immersive, blended, and hybrid learning - Huggett, Cindy (ATD Press, 2023)
In The Facilitator’s Guide to Immersive, Blended, and Hybrid Learning, veteran virtual trainer and learning tech maven Cindy Huggett examines the role of a facilitator in immersive, blended, and hybrid learning environments and offers cutting-edge insights and practical advice on how facilitators can make programs effective and engaging in any scenario. She introduces the new learning experience facilitator role and the skills needed to be successful in today’s modern learning environments. While the shift from traditional classrooms to immersive learning experiences (including immersive, blended, virtual, and hybrid) has exploded in recent years, the supporting technologies and techniques have been evolving over time and now include augmented, mixed, and virtual realities. In fact, immersive, blended, and hybrid learning have become the new reality of training. Cindy walks you through how to facilitate in each of these modalities, covering everything from technology needs to suggested modifications of activities. Throughout, she includes real-life examples of immersive, blended, augmented, virtual, and hybrid learning in action. And she asks the vital question: Is facilitation necessary in immersive learning experiences? The answer is yes, but to be successful, facilitators need to update their skills on an ongoing basis. Prepare yourself with the skills and knowledge to navigate the new world of learning and to make your facilitation shine.